Linha 1 do Metrô de São Paulo: os mais ricos vão ao Paraíso - Oliver Cauã Cauê França Scarcelli; Lucas Coutinho Marcelino da Silva (Confins)
The article aims to analyze the socioeconomic profile of the population served by Line 1 – Blue of the São Paulo Metro at the time of its inauguration. In our research, we mapped the income classes of the households along this line, and also interviewed technicians and managers of Companhia do Metropolitano and other related entities, as well as analyzed newspapers, specialized magazines and technical documents. We found that the subway network was designed to result in the downtown traffic decongestion, thanks to the removal of buses from the streets. This would meet the interests of the middle classes – car-owners – and the tertiary sector – which would benefit from the greater influx of car commuters, in addition to the new Metro users. We verified that the higher income groups were the most favored by the new equipment. There was a striking discrepancy in attendance between classes: while 13 percent of the wealthiest population enjoyed this infrastructure, none of the poorest population benefited from it. Suburban residents were, therefore, condemned to keep commuting by bus and train. Thus, our peripheral urbanization pattern was reproduced, since the poorest are relegated to the districts far from the center, that are often characterized by deficient infrastructure, while the richest occupy the central areas, endowed with urban services. For these reasons, we agree with Francisco de Oliveira (1982), for whom the “middle classes” carried great weight in urban policies as a result of the dismantling of workers’ organizations by the last Brazilian military regime (1964 – 1985). We also subscribe to Silvana Zioni (1999), for whom the transport policies of that authoritarian period only got off the ground because they served the interest of the dominant classes.